Silymarin component 2,3-dehydrosilybin attenuates cardiomyocyte damage following hypoxia/reoxygenation by limiting oxidative stress - Gabrielová, Eva; Křen, Vladimír; Jabůrek, Martin; Modrianský, Martin (Physiological research, 2015)
Ischemic postconditioning and remote conditioning are potentially useful tools for protecting ischemic myocardium. This study tested the hypothesis that 2,3-dehydrosilybin (DHS), a flavonolignan component of Silybum marianum, could attenuate cardiomyocyte damage following hypoxia/reoxygenation by decreasing the generation of reactive oxygen species (ROS). After 5-6 days of cell culture in normoxic conditions the rat neonatal cardiomyocytes were divided into four groups. Control group (9 h at normoxic conditions), hypoxia/reoxygenation group (3 h at 1 % O₂, 94 % N₂and 5 % CO₂followed by 10 min of 10 micromol·l⁻¹DHS and 6 h of reoxygenation in normoxia) and postconditioning group (3 h of hypoxia, three cycles of 5 min reoxygenation and 5 min hypoxia followed by 6 h of normoxia). Cell viability assessed by propidium iodide staining was decreased after DHS treatment consistent with increased levels of lactatedehydrogenase (LDH) after reoxygenation. LDH leakage was significantly reduced when cardiomyocytes in the H/Re group were exposed to DHS. DHS treatment reduced H₂O₂production and also decreased the generation of ROS in the H/Re group as evidenced by a fluorescence indicator. DHS treatment reduces reoxygenation-induced injury in cardiomyocytes by attenuation of ROS generation, H₂O₂and protein carbonyls levels. In addition, we found that both the postconditioning protocol and the DHS treatment are associated with restored ratio of phosphorylated/total protein kinase C epsilon, relative to the H/Re group. In conclusion, our data support the protective role of DHS in hypoxia/reperfusion injury and indicate that DHS may act as a postconditioning mimic.
Keywords: Cell Survival; Oxidative Stress; signální transdukce; Phosphorylation; Signal Transduction; oxidační stres; Protein Kinase C-epsilon; fosforylace; kardiomyocyty; Cytoprotection; novorozená zvířata; reperfuzní poškození myokardu; Protein Carbonylation; cytoprotekce; Antioxidants; zvířata; Myocardial Reperfusion Injury; Cells, Cultured; Myocytes, Cardiac; karbonylace proteinů; proteinkinasa C-epsilon; potkani Wistar; Ischemic Preconditioning, Myocardial; antioxidancia; Animals, Newborn; L-Lactate Dehydrogenase; Rats, Wistar; peroxid vodíku; silymarin; kultivované buňky; Silymarin; Animals; ischemické přivykání; L-laktátdehydrogenasa; Hydrogen Peroxide; viabilita buněk